Prices of Basic Necessities, Impact People's Purchasing Power, and Government Efforts to Suppress Inflation - Junyu, Ma; Satria, Indra (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
Inflation in countries is influenced by various factors that influence it. Inflation, which refers to the decline in the value of a country's currency in comparison to commodities such as gold or foreign currencies, needs to be kept stable at a minimum level. This economic phenomenon, including in the context of Indonesia, causes a general increase in the prices of goods and services. The impact is to encourage people to focus more on work than investing, because inflation has negative effects such as weak efficiency and productivity in production, increased capital costs, and uncertainty regarding future costs and income. One of the efforts that the government can make to increase economic growth is to revive export activities. In fact, this has become an obligation to support economic growth in a country. changes in world commodity prices have a significant impact on various aspects of the economy. One of the main findings is that fluctuations in world commodity prices are not only influenced by economic factors, such as global supply and demand, but also by geopolitical factors, climate change, and other unexpected global events. In the context of the agricultural sector, changes in world commodity prices can have a double impact. Although farmers can benefit when commodity prices rise, they can also be vulnerable to sudden price fluctuations. Adoption of innovative agricultural technology and farmer protection policies can be relevant solutions to overcome this uncertainty. This study uses qualitative research methods. Qualitative research is a series of data filtering as is from the data collected to investigate and understand a phenomenon. In this method, the explanation of the phenomenon will be more descriptive.